A new method for design of the linear gain equalizer based on stancu’s including bernstein polynomials - Chutchavong, V.; Dokyam, T.; Benjangkaprasert, C.; Janchitrapongvej, K. (My University, 2017)
This paper presents an approximation of transfer function for gain equalizer based on the Bernstein-Stancu polynomials operators, which used to equalize the linear gain distortion. As the well-known that the Bernstein-Stancu polynomials have an adjustable parameter more than the classical Bernstein polynomials, it can be used to adjust a response for the best result. As the result, the proposed method to design gain equalizer has a good performance both of low-gain distortion and high-gain distortion. In addition, the stability of desired transfer function is verified by using the Mikhailov’s criterion.
Keywords: Bernstein-Stancu; Linear gain equalizer; Mikhailov’s criterion